Philosophical aspects of 'Murabbi': a contextual analysis with special reference to globalization of education - Paramboor, Jafar; Ibrahim, Mohd Burhan (International Institute for Science, Technology & Education (IISTE), 2013)
In the ongoing process of searching the identity of Islamic education paradigm, theory and practice, there are certain values that should be contemplated with help of the exact traditional methodology of Islamic educational research. Although we could find some alternatives to replace our concrete area of knowledge seeking paradigm, the concept of ‘Murabbi’, the derivative of ‘tharbiyah’ has to be relevantized in the context of globalization of the education. ‘Tharbiya’ in its theoretical aspects cannot be fully related to ‘Murabbi’ in certain conditions through which this paper will be going on. The focus of this paper would be more on how the ‘Murabbi’ has to be philosophically interpreted within the situation of worldwide globalization of education, rather than pointing out the theory and usual application to the present situation. The foundation to establish the concept of ‘‘Murabbi’ as the relevantized character of educator’, the author would analyze some classical educational texts apart from the basic foundations of Islamic education, Qur’Én and Sunnah. The extracts of the globalization concept will be taken out from different available literature in order to make good clarification of how ‘depersonalized knowledge’ can be negatively affect the society in certain aspects.